Phytotoxic and dissuasive activity of Chihuahua desert plants - Ramona PEREZ-LEAL; Maribel TORRES-RAMOS; Maria A. FLORES-CORDOVA; Ana C. GONZALEZ-FRANCO; Adriana HERNANDEZ-RODRIGUEZ; Juan M. SOTO-PARRA; Loreto ROBLES-HERNANDEZ (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2020)
With the purpose of finding plant compounds with the potential use as herbicides and insecticides, a research was realized with the objective of evaluate the phytotoxic and dissuasive activity of four Chihuahua desert plants. The phytotoxic activity evaluation was tested on Lactuca sativa and Lolium perenne, while the dissuasive activity was realized on three species of phytophagous insects: Myzus persicae, Rhopalosiphum padi and Spodoptera littoralis. Raw extracts were used, the solvents hexane, methanol and ethanol of different plants’ organs (root, steam, leaf and flower) of four species: Fouquieria splendens (ocotillo), Larrea tridentate (governor), Astragalus mollissimus (wild grass) and Pachycereus pecten-aboriginum (echo), by the establishment of in vitro bioassays at a concentration of 10 mg/ml extract/solvent. In the toxicity bioassay, the percentage of germination, root and leaf length were measured. The results showed that the leaf extract of L. tridentata had phytotoxic activity for L. sativa, while for L. perenne the phytotoxicity was observed within the ocotillo, governor and echo extracts. In the dissuasive bioassay, each treatment had 20 repetitions with 10 adult insects per repetition. The methanolic extracts of F. splendens leaf and root, ethanolic extract of A. mollisimus sheet and the ethanolic extract of P. pecten-aboriginum stems showed moderate dissuasive response of feeding against M. persicae, presenting a settlement inhibition index of 53.53, 54.35, 60.00 and 48.84% respectively. Nevertheless, the results indicated that none of the 10 extracts tested on S. littoralis showed significant dissuasive properties for this Lepidoptera, while for R. padi all the tested extracts presented dissuasive properties. The treatments of the four vegetable species evaluated showed defensive or dissuasive properties of moderate to strong feeding against the insects M. persicae and R. padi, presenting interesting potential for being used as insecticides, while the tested extracts that presented phytotoxicity for both lettuce and ryegrass present possibilities for the realization of herbicides.